Application of Radio Frequency Identification Technology use in Bhavnagar District Library user’s information- seeking behavior - Dr. Ketan N. Joshi; Dr. Maitry K. Joshi (International Journal of Radio Frequency Innovations, 2025)
Purpose: Bhavnagar District Library to provide faster information services to the users through new technology by using radio frequency identification technology in the information seeking behavior of the user. When it comes to providing information services to users through old traditional methods, it takes time to get information. Today, RFID (Radio frequency identification device) has become very necessary regarding the behavior of getting information through new technology. The users of this public library are made aware of its environment and users. Methodology: This public library was established in 1955 and today has a large collection of information. About 2 thousand users are provided with information services through RFID (Radio frequency identification device) technology regarding information behavior. Students, researchers and local public are using this library. Here survey method is used to collect data and data is collected from librarian by creating questionnaires for data compilation for research. Finding: Increased efficiency through reduced staffing in the library. The exchange service was traditional, which became manual so that users can get quick information. When users come to get information, standing in long queues and doing paperwork, information was available later, which became available in a very short time through paperless operation. Information about whether the 2 information is available in the library can also be obtained. Libraries are developed by Govt. Knowledgeable staff are required to be in the library to operate this technology so that any problems can be dealt with quickly. Library staff and users have benefited greatly through this technology. Originality: Most of the libraries use traditional methods to access information. Not every library is capable of providing information services through RFID method as it requires a large budget. Libraries that have large budgets use this method. RFID technology has been implemented in public libraries regarding the implementation of new technology in the library development programs by the government. This present study is useful for research work related to this topic and information about RFID implementation in every library is available.
Keywords: Application; Behaviour; Bhavnagar District Library; Frequency; Seeking; identification; information; radio; technology; user’s